PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI KEMENKUMHAM DI WILAYAH KERJA LAHAT - Perimansyah, Perimansyah; Marnisah, Luis (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to describe the influence of competence, motivation and discipline partially or simultaneously on the performance of Ministry of Law and Human Rights employees in the Lahat work area. This research method uses quantitative descriptive research. The population is all employees of the Ministry of Law and Human Rights in the Lahat work area totaling 100 employees. The number of samples was determined by Arikunto's formula and the result was 100 respondents. The sampling technique uses the census sampling method. Data collection using questionnaires. Data analysis techniques used by statistical analysis are multiple linear regression tests, t tests, F tests and coefficients of determination. The results showed that competence had a positive and significant effect on the performance of Ministry of Law and Human Rights employees in the Lahat work area. Motivation has a positive and significant effect on the performance of Ministry of Law and Human Rights employees in the Lahat work area. Discipline has a positive and significant effect on the performance of Ministry of Law and Human Rights employees in Lahat's work area. Competence, motivation and discipline have a simultaneous and significant effect on the performance of Kemenkumham employees in the Lahat work area. The implications of competency improvement efforts are that employees are able to establish good communication and cooperation with other employees in the Ministry of Law and Human Rights Institution in Lahat's work area; Employees have conceptual competence and are able to apply it in work and are able to solve problems arising from work. Keywords : Employee Performance, Competence, Motivation, Discipline